Insights, attitudes and perceptions about asthma and its treatment: Findings from a multinational survey of patients from 8 Asia‐Pacific countries and Hong Kong. Issue 6 (25th July 2013) - Thompson, Philip J.; Salvi, Sundeep; Lin, Jiangtao; Cho, Young Joo; Eng, Philip; Abdul Manap, Roslina; Boonsawat, Watchara; Hsu, Jeng‐Yuan; Faruqi, Rab A.; Moreno‐Cantu, Jorge J.; Fish, James E.; Ho, James Chung‐Man
Abstract Background and objective The Asthma Insight and Management (AIM) survey was conducted in North America, Europe, the Asia‐Pacific region and Latin America to characterize patients' insights, attitudes and perceptions about their asthma and its treatment. We report findings from the Asia‐Pacific survey. Methods Asthma patients (≥12 years) from Australia, China, Hong Kong, India, Malaysia, Singapore, South Korea, Taiwan and Thailand were surveyed. Patients answered 53 questions exploring general health, diagnosis/history, symptoms, exacerbations, patient burden, disease management, medications/treatments and patient's attitudes. The Global Initiative for Asthma guidelines were used to assess asthma control. The survey was conducted by random digit telephone dialling (Australia, China and Hong Kong) or by random face‐to‐face interviews (India, Malaysia, Singapore, South Korea, Taiwan and Thailand). Results There were 80 761 households screened. Data from 3630 patients were collected. Wide disparity existed between objective measures of control and patient perception. Reported exacerbations during the previous year ranged from 19% (Hong Kong) to 67% (India). Reported unscheduled urgent/emergency visits to a doctor's office/hospital/clinic in the previous year ranged from 15% (Hong Kong) to 46% (Taiwan). Patients who reported having controlled asthma in the previous month ranged from 27% (South Korea) to 84% (Taiwan). Substantial functional and emotional limitations due to asthma were identified by 13% (South Korea) to 78% (India) of patients. Conclusions Asthma has a profound impact on patients' well‐being despite the availability of effective treatments and evidence‐based management guidelines. Substantial differences across the surveyed countries exist, suggesting unmet, country‐specific cultural and educational needs. A large proportion of asthma patients overestimate their level of control.